Implementing Language-in- Education Policy in Multilingual Mathematics Classrooms: Pedagogical Implications - Halai, Anjum; Karuku, Simon (My University, 2013)
In this paper, we examine selected literature on classroom-based research to understand how students and teachers (re)negotiate the language of interaction in a mathematics classroom when the official medium of instruction is different from the students’ dominant language. We identify the tensions and dilemmas associated with the implementation of language-in-education policy in selected postcolonial Anglophone countries where English is used as a medium of instruction at various stages of formal schooling. We also examine the pedagogical implications of these tensions and dilemmas, paying particular attention to emerging issues of code-switching, translation and ‘safe’ use of language.
Keywords: language-in-education policy; multilingualism; mathematics education